Conceiving kinship : - Bonaccorso, Monica M. E. (Fertility, reproduction and sexuality, 2009)
This compelling study is an in-depth journey, the first of its kind, into how heterosexual, lesbian and gay couples using programmes of gamete donation conceptualize and make Italian kinship. It explores the provision of treatment in clinical and non-clinical settings at a time when Italy was considered the 'Wild-West' of assisted conception.